Control of Ambipolar and Unipolar Transport in Organic Transistors by Selective Inkjet‐Printed Chemical Doping for High Performance Complementary Circuits. (15th August 2014) - Khim, Dongyoon; Baeg, Kang‐Jun; Caironi, Mario; Liu, Chuan; Xu, Yong; Kim, Dong‐Yu; Noh, Yong‐Young
<x xml:space="preserve">Abstract</x> The selective tuning of the operational mode from ambipolar to unipolar transport in organic field‐effect transistors (OFETs) by printing molecular dopants is reported. The field‐effect mobility (μFET) and onset voltage (Von) of both for electrons and holes in initially ambipolar methanofullerene [6, 6]‐phenyl‐C61‐butyric acid methyl ester (PCBM) OFETs are precisely modulated by incorporating a small amount of cesium fluoride (CsF) n‐type dopant or tetrafluoro‐tetracyanoquinodimethane (F4‐TCNQ) p‐type dopant for n‐channel or p‐channel OFETs either by blending or inkjet printing of the dopant on the pre‐deposited semiconductor. Excess carriers introduced by the chemical doping compensate traps by shifting the Fermi level (EF) toward respective transport energy levels and therefore increase the number of mobile charges electrostatically accumulated in channel at the same gate bias voltage. In particular, n‐doped OFETs with CsF show gate‐voltage independent Ohmic injection. Interestingly, n‐ or p‐doped OFETs show a lower sensitivity to gate‐bias stress and an improved ambient stability with respect to pristine devices. Finally, complementary inverters composed of n‐ and p‐type PCBM OFETs are demonstrated by selective doping of the pre‐deposited semiconductor via inkjet printing of the dopants.